ANALISIS PENETAPAN HARGA JUAL DAN VOLUME PENJUALAN IKAN ASAP DI NEGERI HATIVE KECIL KOTA AMBON - Jean Clara Nendissa; Angela Ruban; Kesya Pattimukay (Universitas Pattimura, 2022)
Fish is one of the foods that are rich in protein so it is good to be consumed every day, however, it is a perishable food commodity. One way to overcome this problem is through smoking, in order to provide durability and have a higher selling price. It is an important thing that producers must pay attention to in marketing smoked fish, because it will determine the profit earned for business continuity. The selling price level will affect the quantity of products sold because from the consumer's point of view the price is an indicator of the benefits to be obtained. This study aims to analyze the selling price of smoked fish at Hative Kecil Village and describe the trend of sales volume for the last seven months. Primary data was collected through interviews with 6 traders or producers who actively produce and sell smoked fish and analyzed using the calculation of the production cost using the full costing method and the calculation of selling price using the cost-plus pricing method. The result found that production cost of smoked fish is Rp. 40.920 per smoked fish and the selling price with a mark up of 10% is Rp. 45.000 per smoked fish. The highest sales volume in January was 700 smoked fish per month and the lowest was 280 smoked fish per month in July.